2019
DOI: 10.1186/s12864-019-5579-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles at different stages for formation of pearl sac and pearl in the pearl oyster Pinctada fucata

Abstract: BackgroundThe most critical step in the pearl formation during aquaculture is issued to the proliferation and differentiation of outer epithelial cells of mantle graft into pearl sac. This pearl sac secretes various matrix proteins to produce pearls by a complex physiological process which has not been well-understood yet. Here, we aimed to unravel the genes involved in the development of pearl sac and pearl, and the sequential expression patterns of different shell matrix proteins secreted from the pearl sac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…The shell matrix proteins (SMPs), mostly secreted from OMEs, are directly delivered to the mineralization site via either exosomes or the classical secretory pathway [ 29 , 30 ]. To date, abundant SMPs, which play a vital role in shell and pearl formation, have been identified [ 31 33 ]. However, the process by which pearl formation occurs remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shell matrix proteins (SMPs), mostly secreted from OMEs, are directly delivered to the mineralization site via either exosomes or the classical secretory pathway [ 29 , 30 ]. To date, abundant SMPs, which play a vital role in shell and pearl formation, have been identified [ 31 33 ]. However, the process by which pearl formation occurs remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most studies on exosomes are primarily focused on their roles in disease and immune response [ 34 , 35 ], while exosomes are also involved in shell and pearl formation in molluscs [ 28 ]. In pearl farming, small pieces of mantle tissue from donor oysters are implanted into the gonad of host oysters along with an inorganic bead (termed the ‘nucleus’) for large-scale production of artificial pearls [ 33 , 36 ]. Surgical implantation of the mantle can induce an immune reaction in response to transplantation for the survival of the host oyster [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pearl sac first secretes an organic layer onto the surface of the nucleus ( Taylor and Strack, 2008 ). This is followed by the deposition of successive layers of calcium carbonate, first prismatic and then nacreous, although a large degree of variation can be observed in individual pearls ( Cuif et al, 2008 , 2011 ; Mariom et al, 2019 ). This structural layering is similar to that observed within the pearl oyster shell that also consists of three layers; an outer organic-rich layer (the periostracum), a middle prismatic layer of calcite, and an inner nacreous layer of aragonite.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression analysis of pearl sacs has revealed that pearl formation also involves many of these previously identified SMPs (Wang et al, 2009;Inoue et al, 2010;McGinty et al, 2012;Zhan et al, 2013;Le Luyer et al, 2019); however, pearl sac specific isoforms of known biomineralization genes have also been reported (Kinoshita et al, 2011). Temporal transcriptomic analysis has further revealed that SMPs associated with the prismatic shell layer are up-regulated in the early stages of pearl formation, whereas those associated with the nacreous shell layer are up-regulated later (Mariom et al, 2019), suggesting that the molecular process of pearl formation largely recapitulates that observed in the shell.…”
Section: Introductionmentioning
confidence: 99%
“…The pearl sac first secretes an organic layer onto the surface of the nucleus (Taylor and Strack, 2008). This is followed by the deposition of successive layers of calcium carbonate, first prismatic and then nacreous, although a large degree of variation can be observed in individual pearls (Cuif et al, 2008(Cuif et al, , 2011Mariom et al, 2019). This structural layering is similar to that observed within the pearl oyster shell that also consists of three layers; an outer organic-rich layer (the periostracum), a middle prismatic layer of calcite, and an inner nacreous layer of aragonite.…”
Section: Introductionmentioning
confidence: 99%